PREVALENCE OF UNSOLVED DRINKING PROBLEMS FOR DUI DRIVERS REFERRED FOR MEDICAL EVALUATION IN SWITZERLAND - De Cesare, M.; Jomini, V.; Selz, R.; Mangin, P.; Vaucher, P.; Favrat, B.; Augsburger, M. (International Journal of Research -GRANTHAALAYAH, 2015)
Estimate the proportion of heavy DUI offenders who do not initiate a treatment for their drinking problem before referring to an official medical expertise to recover their driver’s license. Evaluate the proportion of offenders with drinking problems who became abstinent during 6 months within two years after their offense and their characteristics.Between January 2010 and December 2012, data were collected from 1316 consecutive drivers who were referred to an expertise in a legal medicine Swiss institute to recover their driver’s license after driving under the influence of alcohol. 153 offenders were included in the analysis after excluding patients under the influence of other recreational drugs and patients unfit to drive for other medical reasons. Heavy DUI were defined as first time drunk driving offenders with blood alcohol concentration (BAC) ≥2.50 g/kg, or second-time drunk driving offenders within five years with BAC ≥1.60 g/kg in five years, or third-time drunk driving offenders within ten years with BAC ≥0.80 g/kg. 28 subjects of 153 (18%) were considered fit to drive. The rest of the drivers (125, 82%) were considered unfit to drive (drinking problem 77, dissociation alone 48). The majority of offenders (46,4 %) had driving under the influence of alcohol 2 times in the last five years with BAC ≥ 1.60 g/Kg, 65 (42.5%) had BAC ≥ 2.5 and the rest had 3 or more drunk driving offenses. The criteria used for medical and/or psychological assessment are appropriate.